A new species of the genus Chremistica Stål (Hemiptera: Cicadidae) from Vietnam - Thai, Pham Hong; Constant, Jérôme (Academia Journal of Biology, 2013)
A new species of the genus Chremistica Stål, from Vietnam, Chremistica sueuri sp. n. was described and illustrated. Habitus pictures of the adult, illustrations of the male genitalia, a distribution map and biological data are provided. A key to two species of Chremistica from Vietnam, based on the males, was also given. Chremistica sueuri sp.n. was a species of the Chremistica bimaculata group. The new species was distinguishable from all other species of the group by the structure of pygofer. Pygofer oblong in ventral view, dorsally marked with black, and sparsely covered with ochraceous hairs along proximal and laterodistal margins; basal lobe of pygofer S-shaped with apex slightly prominent, upper lobe of pygofer in ventral view with a broad and straight apical margin; a narrowly rounded, slightly inwardly curved, mediodistal corner, and an obtusely angled corner between apical margin of lobe and more distal pygofer margin; uncus bifurcate, lobes elongate and acute apically; dorsal beak acute, brownish black; anal styles and anal tube dark brown